Initial lesson de Pilates promotes acute effect in the flexibility of hamstring muscles - Trevisol, Franciele Casarin (2011)
The method Pilates has been used thoroughly with the purpose of increasing the corporal flexibility, among others. The objective of this study was to verify the acute effect of this training method on the stretching of the hamstring muscles. The sample was composed by 18 individuals selected voluntary randomly, female, with medium age of 26.11 ± 5.48 years, beginners in the method. The subjects were submitted the an evaluation of the range of motion of the hip, pre and post-accomplishment of the class of Pilates, through the equipment Fleximeter, accomplishing three passive repetitions of the movement of flexing of the inferior member (extension) on the hip. The class of Pilates had medium duration of 60 minutes, accomplished individually; using specific apparels of the method, with series of six repetitions each exercise. The results were tabulated and submitted to the statistical analysis through the test student t, where significant increase was verified (p <0.05) for both analyzed inferior members (right inferior limbs - pre class 91.33 ± 8.76, - post class 100.79 ± 14.79 (p = 0.0006); left inferior limbs - pre class 91.29 ± 8.35 - post class 102.70 ± 10.54 (p = 0.000001)). The method Pilates was shown effective, promoting increase of the range of motion of the hamstring muscles in long time, suggests himself then that a long term work can generate great benefits for the earnings of corporal flexibility, however it is still needed studies.